1978
DOI: 10.1021/ac50030a028
|View full text |Cite
|
Sign up to set email alerts
|

Proton induced .gamma.-ray analysis of atmospheric aerosols for carbon, nitrogen, and sulfur composition

Abstract: A technique for the simultaneous quantitative determination of carbon, nitrogen, and sulfur using in-beam y-ray spectrometry has been developed for use with atmospheric aerosol samples. Samples are collected on quartz filters, and the aerosol composltlon is determined by analyzing the y rays emitted following the inelastic scattering of 7.0-MeV protons.Samples are nondestructively irradiated for 1000 s in a helium atmosphere, are not subjected to reduced pressures, and can be used for subsequent analysis. Dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Analysis of Light Elements (GRALE) technique (Macias et al, 1978 Both elemental carbon measurement methods are described by Delumyea et al (1980), and results of the reflectance analyses are reported by Conklin et al (1981). Analysis of the elemental carbon content of these filters using the laboratory reflectometer calibrated by Delumyea et al (1980) introduces a second optical instrument into this experiment in addition to Km samplers .…”
Section: Elemental Carbon Samples Examined By Laboratory Reflectometersmentioning
confidence: 99%
“…Analysis of Light Elements (GRALE) technique (Macias et al, 1978 Both elemental carbon measurement methods are described by Delumyea et al (1980), and results of the reflectance analyses are reported by Conklin et al (1981). Analysis of the elemental carbon content of these filters using the laboratory reflectometer calibrated by Delumyea et al (1980) introduces a second optical instrument into this experiment in addition to Km samplers .…”
Section: Elemental Carbon Samples Examined By Laboratory Reflectometersmentioning
confidence: 99%
“…Samples collected on quartz filters have been analyzed for carbon, nitrogen, and sulfur by determining the 7-rays emitted following the scattering of 7.0 MeV protons. 163 Elemental constituents for S, Cl, Br, K, Ca, Ti, Mn, Fe, Zn, and Pb have been determined for particles >0.25 nm aerodynamic diameter by sampling with cascade impactors and PIXE analysis. 164 This method has been used along with other analytical techniques to distinguish (NH 4 )2SO 4 from H2SO 4 by controlling relative humidity during particle sampling with cascade impactors.…”
Section: Other Instrumental Methodsmentioning
confidence: 99%
“…This type of analysis is called an "absolute analysis." A common practice, however, is to use a 11 relative method 11 of analysis in which only the relative cross sections of a reaction at different incident particle energies are required.…”
Section: G F!:·inciples Of Activation Analvsismentioning
confidence: 99%